QoS-aware services composition in P2PGrid environments. (8th June 2011) - Di Stefano, Antonella; Morana, Giovanni; Zito, Daniele
One of the most significant discussions about service-oriented architectures concerns the creation of new complex services through the composition, under Quality of Service (QoS) constraints, of simple basic services. In fact, although the composition represents a flexible and powerful strategy for the creation of new services, it raises many problems related to the coordination of heterogeneous services offered by different providers. In this paper, the authors propose an innovative strategy for the QoS-aware services composition in Grid oriented Peer-to-Peer networks (P2PGrid), focusing the attention on the phases regarding the creation of the 'execution path' for the composed service and the maintenance of the QoS level during the execution of the services.